Spermatogenesis and nucleolar behavior in Triatoma vandae and Triatoma williami (Hemiptera, Triatominae) - Pereira, N. P. [UNESP]; Alevi, K. C. C. [UNESP]; Mendona, P. P. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2015)
This study describes spermatogenesis in Triatoma vandae and the nucleolar behavior of T. vandae and Triatoma williami, with a cytotaxonomic focus. Analysis of mitotic and meiotic metaphases of T. vandae confirms the species karyotype. T. vandae presents some characteristics during meiosis that differentiate it from T. williami, including the presence of a chromocenter with two sex chromosomes individualized during early prophase, and the presence of a bi-or tripartite corpuscle in polyploid nuclei. It was possible to observe the compaction of chromatin during prophase resulting in holocentric chromosomes. During metaphase, the autosomes presented a ring shape and the sex chromosomes were in the center of the ring. These chromosomes were separated in anaphase. Although it is common, we did not observe the phenomenon of late migration of the sex chromosomes. By means of silver ion impregnation it was possible to describe nucleologenesis in T. vandae and T. williami. In both species we observed persistence of the nucleolar material during meiosis. In addition to the cells in meiotic division, we also observed the presence of polyploid nuclei in the seminiferous tubule walls that nourish the cells during cell division. The nucleolar markings reflect their capacity for synthetic activity. T. vandae and T. williami presented only one nucleolar corpuscle, which reflects low synthetic activity. This study confirms the karyotype of T. vandae, describes characteristics that differentiate T. vandae and T. williami during meiosis, and describes the phenomenon of nucleolar persistence in both species.
Keywords: Nucleolar persistence; Matogrossensis subcomplex; Cytotaxonomy